Novel Imaging of Silver Nanoparticle Uptake by a Unicellular Alga and Trophic Transfer to Daphnia magna - Yan, Neng; Wang, Wen-Xiong (Environmental science & technology, 2021)
Widely applied silver nanoparticles (AgNPs) can have potentially detrimental impacts on aquatic organisms. Unicellular algae as primary producers can interact with AgNPs and initiate their transfer along food chains. Herein, we demonstrate that AgNPs were internalized in a freshwater phytoplankton species , but the entrance pathways varied with their surface coatings. Citrate-coated AgNPs (Cit-AgNPs) were internalized mainly through the apical zone of the cell near the flagella, whereas the aggregation-induced emission fluorogen (AIEgen)-coated AgNPs (AIE-AgNPs) were internalized through endocytosis. The internalized AgNPs were dissolved intracellularly and the released Ag was distributed heterogeneously in the cytoplasm, in contrast to the directly accumulated Ag which displayed a diffuse cytoplasmic distribution pattern. We then further visualized and quantified the trophic transfer of AgNPs from the alga to the zooplanktonic species . Both trophically transferred Ag and AgNPs were concentrated in the gut regions of as a result of the direct ingestion of food particles. After ingestion, about 95% of the trophically transferred Ag was eliminated. Retention of AIE-AgNPs by daphnids was relatively higher than that of Cit-AgNPs due to their lower dissolution of Ag . The present study provides direct evidence for the internalization of AgNPs in unicellular algae and demonstrates that the biological transport of trophically transferred of AgNPs is related to the different surface coatings of NPs.